An Analysis of Public Schools Availability and Affordability in Small Islands (Case Study: Sabang Municipality) - Permana, Sendi; Lubis, Darwin Parlaungan; Yenny, Novida; Permadi, M. Taufik; Milanda, Della Amelia; Nababan, Irson; Maulia, Tria; Halim, Jennifer (Geosfera Indonesia, 2024)
Based on geographical location, Sabang municipality is located in an archipelago far from big cities and has a relatively small population so that the fulfillment of educational facilities needs attention. This study aims to analyze and evaluate the availability and affordability of public elementary schools, junior high schools, and senior high schools in Sabang Municipality. This study uses quantitative and qualitative approaches (mix methods). The analysis of availability and affordability was carried out by calculating serviceability and buffering analysis based on normative reference and was completed with interviews with stakeholders of the Education Office. The results of the study show that for detailed availability, namely elementary schools, junior high schools, and senior high schools are all categorized as deficits, while for detailed affordability, namely, elementary schools are categorized as high, junior high schools are categorized as medium, and senior high schools are categorized as high. The government explained that the availability and affordability of public schools at the elementary schools, junior high schools, and senior high schools levels are adequate and accessible, especially equipped with transportation facilities. The conclusion shows that although this study focuses only on public schools so that it is found that the availability is still a deficit, on the other hand the location of the school can be reached, so it can be interpreted that the location of the school is strategic.